Optimization of power-to-heat flexibility for residential buildings in response to day-ahead electricity price - Golmohamadi, Hessam; Guldstrand Larsen, Kim; Gjøl Jensen, Peter; Riaz Hasrat, Imran (Energy and buildings, 2021)
Increasing the penetration of renewable power in Denmark, demand-side flexibility is offered as a workable solution to hedge against the intermittency and volatility of renewable energy. In the residential sector, heat pumps are economic alternatives for district heating to unlock heat flexibility in response to renewable power availability. This paper proposes a novel economic approach to optimize the heat consumption of a single responsive building with multiple rooms. The suggested approach makes it possible to set different temperature zones for the rooms based on the occupancy patterns. To provide power system flexibility, an Economic Model Predictive Control (EMPC) is designed. The EMPC adjusts heat consumption in response to the electricity price. Integration of the heat flexibility into the power system, two types of heat flexibilities are investigated, including thermal inertia of rooms and thermal storage of buffer. To increase the applicability of the problem, real sensor data of a Danish residential building is used to estimate the constant parameters of the thermal dynamic. To achieve the aim, a model identification method is developed to estimate the constant factors based on the maximum likelihood function. Finally, the performance of the suggested approach is examined in response to the day-ahead electricity price of the Danish Electricity Market. The results showed that the suggested approach not only ensures power system flexibility but also decreases the energy consumption cost of the building up to 37% a week.